VOLUME LALU-LINTAS RENCANA UNTUK GEOMETRIK DAN PERKERASAN JALAN - Hikmat Iskandar (Jurnal Jalan-Jembatan, 2007)
Indication of pavement damages on many roads address to ultimate causes, ie. Overloading of heavy vehicles especially trucks operating along the Pantura lane, North of Java island. Proved which has been occurred, e.g. The collapse of Calendar Hamilton â€œCipunegara Lamaâ€ bridge at Pantura Lane in year 2003. Although, how far the vehicles are overloading, up to now there is no yet formal statement have been published. This paper aims to discuss the design traffic volumes which is covered several topics, ie. basic regulation and methods, both for geometric and pavement design. The discussion concluded that the term of overloading may have two meanings. First, vehicle axle weight is greater than Maximum permissible Axle Load (MST); and second, traffic load design which is expressed as Cumulative Equivalent Standard Axles (CESA) are reached earlier than expected (premature damage). To overcome the problems, it is suggested to count the traffic data covering volumes and loads as basic for design. Keywords : Road damage, Vehicle axle weight, Maximum permissible Axle Load